Wireless energy harvesting‐based spectrum leasing with secondary user selection. Issue 4 (1st March 2017) - Zhai, Chao; Liu, Ju; Zheng, Lina; Wang, Xinhua
Abstract : The authors consider the multiuser cognitive radio network, where a primary link coexists with multiple secondary transmitters (STs) which intend to communicate with an access point (AP). All the STs can harvest the radio frequency energy from the AP, while the primary terminals have the continuous power supply. The primary data transmission and the ST energy harvesting can be simultaneously performed to improve both the spectral and the energy efficiencies. The STs that have correctly decoded the primary data are classified as potential relays. Each potential relay will calculate the channel quality between itself and the primary receiver and the best one is selected to relay the primary data using the harvested energy. Thanks to the cooperation from STs, the primary data can be more reliably transmitted and the throughput requirement of primary system can be more easily satisfied in a shorter time, and as a reward all the STs except the selected one can transmit their own data to the AP in the remaining time. To facilitate the primary data cooperation, the energy transfer and the secondary data transmission, the optimal time allocation can be determined through maximising the STs' throughput while guaranteeing the throughput of primary system.